Green reversed‐phase HPLC development strategy: Application to artesunate and amodiaquine analysis. Issue 24 (12th November 2020) - Yabré, Moussa; Ferey, Ludivine; Somé, Touridomon Issa; Mercier, Olivier; Gaudin, Karen
Abstract: A green analytical chemistry strategy is described to develop a reversed‐phase high‐performance liquid chromatography method for amodiaquine and artesunate analysis using ethanol‐based mobile phases. This method development was particularly challenging due to the basicity of amodiaquine and low UV absorption of artesunate, leading to peak asymmetry and detection issues, respectively. UV detection concern was even more challenging due to the baseline drift observed with ethanol in gradient mode. Several green pH modifiers were selected for their ecofriendly character and their impact on peak shape and detection was investigated. The screening of various stationary phases (19 columns) appeared as a relevant and necessary approach to reach satisfactory peak shape of basic compounds. To support the results of this study, some additional compounds related to artesunate and amodiaquine structures were included. Methods were optimized and validated using total error approach with a mobile phase composed of ethanol and 10 mM formic acid using three different stationary phases from different manufacturers, providing flexibility of the quality control approach. Method greenness was assessed using the National Environmental Methods Index, the Green Analytical Procedure Index, and the Analytical Eco‐Scale. Finally, artesunate and amodiaquine were successfully analyzed in fixed dose combination tablets.